Anything goes for participant, patient and public involvement in youth mental health research - Marian J. Bakermans‐Kranenburg; Marinus H. vanIJzendoorn (JCPP Advances)
Abstract Background Participant and Public Involvement in youth mental health research aims at making research more responsive to the needs of youth struggling with mental health issues, their parents, and mental health professionals and other stakeholders. Do characteristics of Patient and Public Involvement (PPI) in youth mental health research align with transparency and replication prerequisites as necessary conditions for translation? Relatedly, the question is addressed whether co‐authorship should be assigned to youth involved in the study. Methods Here we address these questions re‐visiting 50 PPI studies included in two recent systematic reviews of PPI on characteristics that are pertinent to questions about transparency, replicability, translatability, and co‐authorship in PPI research. Results Almost two‐third of the studies on youth mental health incorporating PPI translate their results to policy or practice, mostly as recommendations but sometimes also by dissemination of (online) interventions. At the same time the authors of a substantial majority of the studies (70%) also suggest the need for further work on their results, for example, in randomized controlled trials to validate the outcome of their exploratory inquiry. Only a quarter of the studies using PPI met the conditions for replicability, thus a majority of the PPI studies suggest premature translation of results. Authorship to involved participants was assigned in 24% of the studies. Conclusions “Anything goes” for PPI in an exploratory stage to generate fruitful hypotheses. Translation of the findings of PPI studies however require a firm evidence base of replicated results. Radical merging of research and action in participatory action research seems incompatible with replicable and therefore translatable inquiry. Assigning co‐authorship to PPI representatives is often at odds with current guidelines for authorship. More evidence from randomized trials on the translational impact of PPI is needed before grant foundations should require PPI in grant proposals.